he Use of Red Algae Wastes as Bio Adsorbent for Heavy Metals Removal - Abdul Rahim, Mohamed Hyrul Amry (Universiti Teknologi PETRONAS, 2017)
e use of natural adsorbents in heavy metals removal from wastewater turning into an incredible concern these days as the effluents from municipal and heavy industrial sectors for example, electroplating, mining operation, tanneries, refining, batteries production, and so on are generally being developed. This starts such a great amount of negative impact to the ecosystem since heavy metals can produce numerous health issues particularly to human by means of food consumption and also influence the serenity of natural biological system. Numerous researches have been done regarding the utilization of algae waste since algae can act as natural bio-adsorbents to replace the current conventional methods in heavy metal removals. This project is focused on the removal of Lead and Zinc from the wastewater.